Principles of Ensuring the Information Security of The Country - URAKOVICH, MUKHAMMADIEV JABBOR; AKBAROVICH, BAHRAMOV SAYFIDDIN; MAKHMUT, MAMATOV; SHAVKATOVNA, MAMATKULOVA MUYASSAR; HUSNUTDINOVNA, NAZIROVA DILOROM (The journal of contemporary issues in business and government, 2021)
The problem of ensuring the information security of any state is one of the most important aspects of its foreign policy, since it is the information sphere that is at present the most important object of application of the activities of various participants in international relations. The information sphere is the least formalized environment of human activity due to the nature of information and the properties of consciousness, which are hard to yield to rigid external algorithms, except for those cases when a person as a carrier of consciousness is in a state of unfreedom. Information security is the most important element in ensuring the vital interests of our country, since threats to the country’s national security in all areas of the state’s activities are increasingly being implemented through the information environment. The article analyzes the main approaches to providing information security of the country, formulated the goal, tasks, functions, principles of ensuring information security of the country.